Review of potential structural applications of hybrid fiber Engineered Cementitious Composites - Maalej, M.; Quek, S.; Ahmed, Shaikh; Zhang, J.; Lin, V.; Leong, K. (Elsevier BV, 2012)
This paper reviews some of the recent research work focusing on assessing the performance of hybrid fiber Engineered Cementitious Composite (ECC) materials in a number of potential structural applications. A summary of the design and characteristics of such materials is presented followed by a review of recent potential applications of hybrid fiber ECC. The reviewed applications include the use of hybrid fiber ECC for designing impact and blast resistant protective panels, strengthening of unreinforced masonry (URM) walls, strengthening of RC beams, and enhancing corrosion durability of RC beams. The review demonstrates that hybrid fiber ECC can significantly enhance the performance of structures incorporating these materials.